A4_1 Blowing Up Earth - Coulson, Rebecca; Sier, Anya; Shehzad, Habeebah; Wayman, James; Nuttall, Heather (Physics Special Topics, 2022)
In this paper, the time it takes to blow up an inflatable ball, the size of earth, on different planets is calculated. It was determined it would take the least amount of time on Mars with a time of 3.139 ± 0.0564 Trillion years. It would take the longest on Venus with a time of 17.89 ± 3.215 Trillion years.